Functional outcome and muscle wasting in adults with tetanus - Trung, TN; Duoc, NVT; Nhat, LTH; Yen, LM; Hao, NV; Truong, NT; Duong, HTH; Thuy, DB; Phong, NT; Tan, LV; Puthucheary, ZA; Thwaites, C (Oxford University Press, 2019)
Background In many countries, in-hospital survival from tetanus is increasing, but long-term outcome is unknown. In high-income settings, critical illness is associated with muscle wasting and poor functional outcome, but there are few data from resource-limited settings. In this study we aimed to assess muscle wasting and long-term functional outcome in adults with tetanus. Methods In a prospective observational study involving 80 adults with tetanus, sequential rectus femoris ultrasound measurements were made at admission, 7 days, 14 days and hospital discharge. Functional outcome was assessed at hospital discharge using the Timed Up and Go test, Clinical Frailty Score, Barthel Index and RAND 36-item Short Form Health Survey (SF-36) and 3 and 6 months after discharge using the SF-36 and Barthel Index. Results Significant muscle wasting occurred between hospital admission and discharge (p<0.01), particularly in severe disease, where a median 23.49% (interquartile range 10.01–26.07) reduction in rectus femoris cross-sectional area occurred in those with severe (Ablett grades 3 and 4) disease. Muscle mass at discharge was related to objective and subjective measures of physical and emotional function at discharge and 3 and 6 months after discharge. In patients >70 y of age, functional recovery at 6 months was reduced compared with younger patients. Hospital-acquired infection and age were risk factors for muscle wasting. Conclusions Significant muscle wasting during hospitalization occurred in patients with tetanus, the extent of which correlates with functional outcome.